Short-term costs of integrating whole-genome sequencing into primary care and cardiology settings: a pilot randomized trial. (December 2018) - Christensen, Kurt; Vassy, Jason; Phillips, Kathryn; Blout, Carrie; Azzariti, Danielle; Lu, Christine; Robinson, Jill; Lee, Kaitlyn; Douglas, Michael; Yeh, Jennifer; Machini, Kalotina; Stout, Natasha; et al.
Abstract Purpose Great uncertainty exists about the costs associated with whole-genome sequencing (WGS). Methods One hundred cardiology patients with cardiomyopathy diagnoses and 100 ostensibly healthy primary care patients were randomized to receive a family-history report alone or with a WGS report. Cardiology patients also reviewed prior genetic test results. WGS costs were estimated by tracking resource use and staff time. Downstream costs were estimated by identifying services in administrative data, medical records, and patient surveys for 6 months. Results The incremental cost per patient of WGS testing was 5, 098 in cardiology settings and 5, 073 in primary care settings compared with family history alone. Mean 6-month downstream costs did not differ statistically between the control and WGS arms in either setting (cardiology: difference = −1, 560, 95% confidence interval −7, 558 to 3, 866, p = 0.36; primary care: difference = 681, 95% confidence interval −884 to 2, 171, p = 0.70). Scenario analyses showed the cost reduction of omitting or limiting the types of secondary findings was less than 69 and 182 per patient in cardiology and primary care, respectively. Conclusion Short-term costs of WGS were driven by the costs of sequencing and interpretation rather than downstream health care. Disclosing additional types of secondary findings has a limited cost impact following disclosure.